A 112 Gb/s Radiation-Hardened Mid-Board Optical Transceiver in 130-nm SiGe BiCMOS for Intra-Satellite Links - Giannakopoulos, Stavros; Sourikopoulos, Ilias; Stampoulidis, Leontios; Ostrovskyy, Pylyp; Teply, Florian; Tittelbach-Helmrich, K.; Panic, Goran; Fischer, Gunter; Grabowski, Alexander; Zirath, Herbert; Ayzac, Philippe; Venet, Norbert; et al. (Frontiers in Physics, 2021)
We report the design of a 112 Gb/s radiation-hardened (RH) optical transceiver applicable to intra-satellite optical interconnects. The transceiver chipset comprises a vertical-cavity surface-emitting laser (VCSEL) driver and transimpedance amplifier (TIA) integrated circuits (ICs) with four channels per die, which are adapted for a flip-chip assembly into a mid-board optics (MBO) optical transceiver module. The ICs are designed in the IHP 130 nm SiGe BiCMOS process (SG13RH) leveraging proven robustness in radiation environments and high-speed performance featuring bipolar transistors (HBTs) with fT/fMAX values of up to 250/340 GHz. Besides hardening by technology, radiation-hardened-by-design (RHBD) components are used, including enclosed layout transistors (ELTs) and digital logic cells. We report design features of the ICs and the module, and provide performance data from post-layout simulations. We present radiation evaluation data on analog devices and digital cells, which indicate that the transceiver ICs will reliably operate at typical total ionizing dose (TID) levels and single event latch-up thresholds found in geostationary satellites.